2020
DOI: 10.1111/cei.13547
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte subsets early predict mortality in a large series of hospitalized COVID-19 patients in Spain

Abstract: Disbalanced lymphocyte subpopulations are early markers of mortality in our series of 701 SARS‐CoV‐2 infected patients, when severe lymphopenia has yet to develop. If available, the study of lymphocyte subsets by flow cytometry is recommended to identify high‐risk COVID‐19 patients at hospital admission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 47 publications
2
33
2
Order By: Relevance
“…Furthermore, lymphocyte increment by one unit decreases the risk of death by 10% among COVID-19 hospitalized patients. This finding is supported by studies conducted in Italy, 76 Mexico, 90 Spain, 91 France, 40 and Wuhan. 92 Studies showed that as COVID-19 clinical stages advance, the lymphocyte count decreases, 93–95 thus, as the clinical stages of COVID-19 patients advance to severe and critical, the clinical outcome could be bad.…”
Section: Discussionsupporting
confidence: 63%
“…Furthermore, lymphocyte increment by one unit decreases the risk of death by 10% among COVID-19 hospitalized patients. This finding is supported by studies conducted in Italy, 76 Mexico, 90 Spain, 91 France, 40 and Wuhan. 92 Studies showed that as COVID-19 clinical stages advance, the lymphocyte count decreases, 93–95 thus, as the clinical stages of COVID-19 patients advance to severe and critical, the clinical outcome could be bad.…”
Section: Discussionsupporting
confidence: 63%
“…These results were consistent with the study conducted in Spain, which demonstrated that there were no differences in CD19 + B cell percentages between the survivor and non-survivor groups 42 . The plausible explanation for this discrepancy may be due to the direct infection of T lymphocytes by SARS-CoV-2, cytokine-mediated lymphocyte trafficking into infected tissues, or lymphocyte exhaustion in the peripheral blood 42 , 43 . All of these hypotheses remain to be proven in further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Cantenys-Molina et al [28] demonstrated that significant reduction of CD3 + CD4 + T cell percentages was associated with mortality and insignificant variations in CD19 + B cell percentages. However, no significant reduction was detected in CD3 + CD8 + T cells and CD56 + NK cell counts which disagreed with our findings.…”
Section: Discussionmentioning
confidence: 99%